PENGEMBANGAN MEDIA MINIATUR PUZZLE 3 DIMENSI (MP3D) PADA MATERI SISTEM TATA SURYA KELAS VII SMP - Khoiro, Safiratul; Rakhmawan, Aditya; Ahied, Mochammad; Wahyuni, Eva Ari; Hartiningsih, Try (Natural Science Education Research, 2024)
Miniature Puzzle 3 Dimensions (MP3D) is one form of learning media presentation that has been systematically assembled in the form of a miniature collaborated with puzzles so that learning on solar system material grade VII can be conveyed properly and clearly. The purpose of this study was to produce MP3D media and determine the level of feasibility and student response to MP3D media. This type of research is development research using the ADDIE development model. The population in this study were seventh grade students of SMPN 3 Kamal with samples of VII-B and VII-D classes. Sampling using purposive sampling technique. The instruments used were media expert validation sheets, science teachers and student response questionnaires. The results showed that: 1) The results of the validity of the media aspect amounted to 94.37% and the reliability value of 97.38% with a very valid and very reliable category. 2) Student responses to MP3D media in 3 trial groups, obtained a percentage value of 88.55% in individual trials of 2 students, 88.81% in small group trials of 8 students and 91.27% in large group trials of 32 students, the three trials had a very good category. We concluded that the using of MP3D media is feasible to use in learning.